Delirium in acute ischemic stroke: risk factors, sequelae, and pathogenetic treatment - Igor V. Litvinenko; Yuriy V. Khlystov; Nikolay V. Tsygan; Miroslav M. Odinak; Evgeny S. Kurasov; Kirill V. Sapozhnikov (Анналы клинической и экспериментальной неврологии)
Introduction. Delirium, or an acute confusional state, is a common complication affecting between 10 and 48% of acute stroke patients. In the acute phase of stroke, delirium contributes to prolonged hospital stays, higher treatment costs and in-hospital and long-term mortality, increased risk of disability, and reduced potential for post-stroke rehabilitation.